Anti-programmed-death-receptor-1 (PD-1) antibody (Pembrolizumab) induced pancreatitis diagnosed on 18F-FDG PET/CT - Sharjeel Usmani; Anjali Jain; Khulood Al Riyami; Raza Sayani; Vipin V Jayakrishan (Journal of the Pakistan Medical Association, 2024)
Immunotherapy related adverse events are commonly seen with immune check point inhibitors therapy. We report the case of a 40-year-old female diagnosed with stage IVB endometroid grade III endometrial cancer, on pembrolizumab immunotherapy, an anti-programmed-death-receptor-1 (PD-1) antibody. Patient was referred for 18F-FDG PET/CT for restaging. 18F-FDG PET/CT demonstrated diffuse increased FDG uptake throughout the body of the pancreas associated with fat stranding in the peripancreatic region, suggestive of pembrolizumab-induced pancreatitis. The diagnosis was confirmed by elevated amylase and lipase levels. Immune-related adverse events are frequently identified on 18F-FDG PET-CT, which may lead to early diagnosis, close clinical follow-up, and appropriate clinical management of immune-related adverse events. Key Words: 18F-FDG PET/CT; pembrolizumab; pancreatitis; anti-programmed-death-receptor-1 (PD-1) antibody